(untitled) (Ameghiniana, 2014)
The Order Notoungulata is a large group of endemic mammals widespread throughout the Cenozoic of South America. Among them, the Family Homalodotheriidae is one of the less abundant and diverse, and geographically more restricted. Its record ranges from early Oligocene to late Miocene, but only a few genera were described, mainly known from Patagonia. This paper deals with the first homalodotheriid remains recovered from Deseadan levels outside Patagonia. The material comes from Quebrada Fiera, a late Oligocene locality in southern Mendoza Province(Argentina), and mainly consists of postcranial elements. A comparative study lead to its placement in the Patagonian genus Asmodeus Ameghino, but with some significant differences from Asmodeus osborni Ameghino. Thus a new species –Asmodeus petrasnerus sp. nov.– is proposed for the taxon from Mendoza. It is characterized by: calcaneum with a subtriangular navicular facet, ectal facet with concave medial border, and not projected anterodistal end; astragalus with distal facet more medially placed than in A. osborni, without astragalar foramen, and with astragalar groove expanded; cuboid without contact with the astragalus; Mc III with posteriorly expanded proximal facet; and Mc IV with medial facets separated to the proximal edge. The material from Mendoza provides new data on the postcranial anatomy of Asmodeus and allows completing the diagnosis of this genus. The record of A. petrasnerus sp. nov. in Quebrada Fiera increases the diversity and the geographical distribution of the genus and the family during the late Oligocene.